Examining Perceptions of Technological Pedagogical Content Knowledge (TPACK): A Perspective from Indonesian Pre-service Teachers - Irwanto, I.; Redhana, I. W.; Wahono, B. (Jurnal Pendidikan IPA Indonesia, 2022)
Understanding pre-service teachers’ perceived technological pedagogical content knowledge (TPACK) is important to better prepare them for their future STEM-related careers. Thus, this study aims to examine pre-service teachers’ perceptions of TPACK in relation to their age, gender, and grade level. To achieve this goal, a cross-sectional survey design was used in this quantitative non-experimental research. Participants included 481 (136 male; 345 female) pre-service teachers from four public and private universities in Indonesia. A 27-item PTTPACK Survey was used to gather data. Independent t-test, ANOVA, and Person’s correlation were executed to analyze the data. The findings suggested that pre-service teachers performed the highest self-confidence level in pedagogy knowledge and the lowest in technology knowledge. They rated themselves above four on a five-point scale. No significant differences for all TPACK dimensions were found in terms of gender and age. In addition, there was a significant difference between pre-service teachers who were at the postgraduate level and those at the undergraduate level. Moreover, a high positive and significant correlation existed between all six TPACK domains. It is suggested that pre-service teacher preparation programs should facilitate pre-service STEM teachers how to integrate pedagogy, content, and technology together to create effective technology-enhanced learning in their subjects.